Quantitative Analysis of Nitrofuran Metabolites and Chloramphenicol in Shrimp Using Acetonitrile Extraction and Liquid Chromatograph-Tandem Mass Spectrometric Detection: A Single Laboratory Validation. (27th November 2019) - An, Haejung; Parrales, Lenin; Wang, Kai; Cain, Teresa; Hollins, Ralph; Forrest, Douglas; Liao, Benjamin; Paek, Han Chol; Sram, Jacqueline
Abstract: A method was developed and validated for the simultaneous analysis of chloramphenicol and nitrofuran metabolites in shrimp according to the guideline established by the U.S. Food and Drug Administration Office of Foods and Veterinary Medicine. The extraction steps following the overnight hydrolysis and derivatization are simpler than the conventional ethyl acetate extraction method. The main steps are neutralization of hydrolysates, addition of acetonitrile for extraction, and salting out of organic phase from the acetonitrile-aqueous mixture. Extracts are analyzed for chloramphenicol and nitrofuran metabolites by LC-MS/MS in a single injection with polarity switching between the positive electrospray ionization (ESI) mode for the nitrofurans and the negative ESI mode for chloramphenicol. Recoveries calculated using an extracted matrix calibration curve and labeled internal standards for chloramphenicol and nitrofurans ranged from 98.6 to 109.2% with RSDs less than 18%. This method that combines the analysis of chloramphenicol with the nitrofurans was shown to generate analytical results similar to those obtained using the individual drug-class analytical methods currently used for the analysis of chloramphenicol or nitrofurans in shrimp.